Clinical characteristics, comorbidities and outcomes among persons with HIV hospitalized with coronavirus disease 2019 in Atlanta, Georgia. (1st October 2020) - Collins, Lauren F.; Moran, Caitlin A.; Oliver, Nora T.; Moanna, Abeer; Lahiri, Cecile D.; Colasanti, Jonathan A.; Kelley, Colleen F.; Nguyen, Minh L.; Marconi, Vincent C.; Armstrong, Wendy S.; Ofotokun, Ighovwerha; Sheth, Anandi N.
Abstract : Background: There are limited data describing the presenting characteristics and outcomes among US persons with HIV (PWH) requiring hospitalization for coronavirus disease 2019 (COVID-19). Methods: We performed a case series of all PWH sequentially admitted with COVID-19 from 8 March 2020 to 23 April 2020 at three hospitals in Atlanta, Georgia. Sociodemographic, clinical and HIV-associated characteristics were collected. Results: Of 530 confirmed COVID-19 cases hospitalized during this period, 20 occurred among PWH (3.8%). The median age was 57 (Q1–Q3, 48–62) years, 65% were men, and 85% were non-Hispanic Black. Presenting median symptom duration was 5 (Q1–Q3, 3–7) days; cough (90%), fever (65%), malaise (60%) and dyspnea (60%) were most common. On admission, 40% of patients required oxygenation support and 65% had an abnormal chest radiograph. Median length of hospitalization was 5 (Q1–Q3, 4–12) days, 30% required intensive care, 15% required intubation, and 15% died. Median CD4 + cell count prior to admission was 425 (Q1–Q3, 262–815) cells/μl and 90% of patients had HIV-1 RNA less than 200 copies/ml. Half of the patients had at least five comorbidities; hypertension (70%), dyslipidemia (60%) and diabetes (45%) were most prevalent. All three patients who died had CD4 + cell count more than 200, HIV suppression and each had a total of five comorbidities. Conclusion: The multisite series in the Southern United States provides characteristics and early outcomes of hospitalized PWH with COVID-19. Nearly all patients had controlled HIV and a high comorbidity burden. Additional study of COVID-19 among PWH is needed to determine the role of age, comorbidities and HIV control in mediating COVID-19 presentation and its sequelae.